2012
DOI: 10.1053/j.gastro.2012.07.099
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2–Mediated Intestinal Injury and Enteric Tumor Necrosis Factor Receptor I Contribute to Liver Fibrosis in Mice

Abstract: Background & Aims Progression of liver fibrosis in experimental models depends on gut-derived bacterial products, but little is known about mechanisms of disruption of the mucosal barrier or translocation. We used a mouse model of cholestatic liver disease to investigate mechanisms of intestinal barrier disruption following liver injury. Methods Liver fibrosis and bacterial translocation were assessed in Toll-like receptor (TLR)2- and tumor necrosis factor receptor (TNFR)I-deficient mice subjected to bile du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 33 publications
3
86
1
1
Order By: Relevance
“…This is in contrast to a murine model of cholestatic liver disease where bacterial translocation was dependent on TLR-2 and TNFRI pathways, suggesting that the bile duct ligation model differs from molecular pathways associated with bacterial translocation in human non-cholestatic cirrhosis [24].…”
Section: Discussioncontrasting
confidence: 73%
“…This is in contrast to a murine model of cholestatic liver disease where bacterial translocation was dependent on TLR-2 and TNFRI pathways, suggesting that the bile duct ligation model differs from molecular pathways associated with bacterial translocation in human non-cholestatic cirrhosis [24].…”
Section: Discussioncontrasting
confidence: 73%
“…In fact, similar results had been obtained in the past showing the antiinflammatory properties of TLR-2 [27][28][29] and the induction of a pro-inflammatory cytokine response by B. breve after blocking TLR-2 [30]. In contrast to this and the previously mentioned studies, an inflammatory downregulation in monocytes from lamina propria in TLR2-deficient mice with bile duct ligation has been reported [31]. Several aspects, such as the distinct experimental model used and the intestinal monocyte population used rather than ILs, may explain this difference.…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that intestinal inflammation mediated by inflamed cells in the lamina propria is involved in upregulation of intestinal permeability leading to enhanced translocation of bacteria or their products (38). Besides, compromised antimicrobial peptide production has also been reported to predispose hosts to bacterial translocation in experimental cirrhosis (42).…”
Section: Discussionmentioning
confidence: 99%
“…To assess bacterial translocation from gastrointestinal segments, we used a modified intestinal loop model as previously described (35)(36)(37)(38). After anesthesia, a midline laparotomy incision was made.…”
Section: Methodsmentioning
confidence: 99%